2018
DOI: 10.1039/c7sc05320g
|View full text |Cite
|
Sign up to set email alerts
|

Redox and photocatalytic properties of a NiII complex with a macrocyclic biquinazoline (Mabiq) ligand

Abstract: Upon irradiation with visible light, the NiII complex 1 is converted to the reduced form 2 in the presence of NEt3. The Ni-based photosensitizer catalyzes the cyclization of a bromoalkyl-substituted indole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 45 publications
3
58
0
4
Order By: Relevance
“…Our study complements ongoing research on photoactive complexes with other Earth-abundant metal elements such as Fe, [9][10][11][12][13][14][15] Cu, [40][41][42][43][44][45][46][47][48][49][50] Cr, [51][52][53][54] Co, 55 Ni, [56][57][58] Zr, [59][60] W, [34][35][61][62][63] and Ce, 64 as well as current research on new metal-free organic photosensitizers. [65][66][67][68][69]…”
Section: Long-lived Strongly Emissive and Highly Reducing Excited Stsupporting
confidence: 55%
“…Our study complements ongoing research on photoactive complexes with other Earth-abundant metal elements such as Fe, [9][10][11][12][13][14][15] Cu, [40][41][42][43][44][45][46][47][48][49][50] Cr, [51][52][53][54] Co, 55 Ni, [56][57][58] Zr, [59][60] W, [34][35][61][62][63] and Ce, 64 as well as current research on new metal-free organic photosensitizers. [65][66][67][68][69]…”
Section: Long-lived Strongly Emissive and Highly Reducing Excited Stsupporting
confidence: 55%
“…The addition of THF to this sample of 1 afforded a homogeneous frozen glass at 140 K. The spectrum is quintessentially that of a Cu II species with an unpaired electron in the Previous studies have shown that it is possible to photoreduce the Ni II -Mabiq complex upon irradiation with visible light in the presence of a sacrificial electron donor. 36 We thus examined whether the cupric containing 1 and 3 exhibited similar photochemical behaviour (Scheme 2). internal standard of ferrocenium/ferrocene (Fc +/0 ).…”
Section: Synthesis and Solid-statementioning
confidence: 99%
“…[33][34][35] The molecule also exhibits promise for photoredoxcatalysis, as recently demonstrated for the [Ni II (Mabiq)] + complex. 36 Furthermore, the Mabiq ligand is distinct from the majority of N4-macrocycles in that it provides a second peripheral metal binding site. This latter feature has so far been underexplored.…”
mentioning
confidence: 99%
“… 14 Although they are inexpensive and well-compatible in photochemical reactions, 15 nickel complexes themselves have only been reported as potential photoredox catalysts very recently. 16 , 17 Herein, we wish to reveal our discovery on using a readily available Ni II –DBFOX complex as a bifunctional catalyst for visible-light-promoted enantioselective reactions between α,β-unsaturated carbonyl compounds and α-silylamines ( Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%